2019
DOI: 10.1186/s13098-019-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin treatment and new-onset diabetes mellitus: a population based case–control study

Abstract: Background Several studies suggest that statin may increase the risk of new-onset diabetes mellitus (NODM). This study aimed to evaluate the association between the duration and recent use of statin, and the risk of NODM, based on population-based data sets. Methods We used the South Korean National Health Insurance Service National Sample Cohort database for this nationwide case–control study. Of the 1 million participants, 6417 participants with NODM in 2012–2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The incidence of new-onset or worsening diabetes was lower in the bempedoic acid group than in the placebo group; overall, cases of new or worsening diabetes occurred in 4.0% of bempedoic acid-treated patients compared with 5.6% of placebo-treated patients (overall safety pool, nominal p < 0.05) [39]. By contrast, statins have been associated with an increased incidence of new-onset diabetes compared with placebo [50][51][52][53].…”
Section: Clinical Considerationsmentioning
confidence: 93%
“…The incidence of new-onset or worsening diabetes was lower in the bempedoic acid group than in the placebo group; overall, cases of new or worsening diabetes occurred in 4.0% of bempedoic acid-treated patients compared with 5.6% of placebo-treated patients (overall safety pool, nominal p < 0.05) [39]. By contrast, statins have been associated with an increased incidence of new-onset diabetes compared with placebo [50][51][52][53].…”
Section: Clinical Considerationsmentioning
confidence: 93%
“…With common and long-term use of such medications, a number of adverse effects have been reported. Specifically, statins have been associated with liver damage (Aguirre et al, 2013), muscle discomfort (Pirillo and Catapano, 2015) and diabetes (Kim D. W. et al, 2019;Kim Y. S. et al, 2019). Yet, how the medication contributes to diabetes risk and impaired glucose metabolism is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of statins in reducing diabetes mellitus (DM) has also been evaluated. According to the observations, long-term or first-time use of statins was not associated with DM incidence [70]. Nonetheless, a recent study on short-term consumption of statins (in comparison to those that have never used statins) showed that it might promote susceptibility to the development of DM [71].…”
Section: Statinsmentioning
confidence: 99%